Sulfonylurea Treatment Before Genetic Testing in Neonatal Diabetes: Pros and Cons - Carmody, David; Bell, Charles D.; Hwang, Jessica L.; Dickens, Jazzmyne T.; Sima, Daniela I.; Felipe, Dania L.; Zimmer, Carrie A.; Davis, Ajuah O.; Kotlyarevska, Kateryna; Naylor, Rochelle N.; Philipson, Louis H.; Greeley, Siri Atma W. (The journal of clinical endocrinology and metabolism, 2014)
Context:Diabetes in neonates nearly always has a monogenic etiology. Earlier sulfonylurea therapy can improve glycemic control and potential neurodevelopmental outcomes in children with KCNJ11 or ABCC8 mutations, the most common gene causes.Objective:Assess the risks and benefits of initiating sulfonylurea therapy before genetic testing results become available.Design, Setting, and Patients:Observational retrospective study of subjects with neonatal diabetes within the University of Chicago Monogenic Diabetes Registry.Main Outcome Measures:Response to sulfonylurea (determined by whether insulin could be discontinued) and treatment side effects in those treated empirically.Results:A total of 154 subjects were diagnosed with diabetes before 6 months of age. A genetic diagnosis had been determined in 118 (77%), with 73 (47%) having a mutation in KCNJ11 or ABCC8. The median time from clinical diagnosis to genetic diagnosis was 10.4 weeks (range, 1.6 to 58.2 wk). In nine probands, an empiric sulfonylurea trial was initiated within 28 days of diabetes diagnosis. A genetic cause was subsequently found in eight cases, and insulin was discontinued within 14 days of sulfonylurea initiation in all of these cases.Conclusions:Sulfonylurea therapy appears to be safe and often successful in neonatal diabetes patients before genetic testing results are available; however, larger numbers of cases must be studied. Given the potential beneficial effect on neurodevelopmental outcome, glycemic control, and the current barriers to expeditious acquisition of genetic testing, an empiric inpatient trial of sulfonylurea can be considered. However, obtaining a genetic diagnosis remains imperative to inform long-term management and prognosis.